Kronologija macesna (Larix decidua Mill.) za območje jugovzhodnih Alp - Levanič, Tom (Zbornik gozdarstva in lesarstva, 2005)
A 333 years long living larch tree ring chronology for the Southeastern Alps is presented. The highest chronology depth is 74, more than four samples are present in 95% of the entire length, and only the first eight years are based only on a single tree. Six sampling locations were chosen along the Alpine ridge in Slovenia, i.e.: Jezersko (two plots), Komna, Vršič, Veža, Viševnik and Uskovnica. Compiled chronology synchronise well with the selection of foreign chronologies (France, Italy, Austria, Germany and Switzerland). New Slovene larch chronology has 34 positive and 87 negative pointer years. Preliminary tests revealed good climatic signal as well. Although some very old trees (400 yrs. +) have been found, cored and measured, they were not included in this chronology due to many missing rings and various growth irregularities.
Keywords: dendrokronologija; Larix decidua Mill.; macesen